PERANCANGAN SISTEM INFORMASI JADWAL KERETA API TAMBAHAN DI PT. KERETA API INDONESIA (PERSERO) DAERAH OPERASI 2 BANDUNG - Rini Tisnawati (INFOKOM (Informatika & Komputer), 2018)
This research aims to determine the process of running systems as well as design andbuild additional train schedule information system at PT. Kereta Api Indonesia (Persero)Operation Area 2 Bandung.Based on the research results, the process of calculating the travel time of an additionaltrain is still manually, so the calculation process to be slow and complicate in preparingreports and filing additional train schedule.Research methods used are surveys observations to research sites, interviews andliterature review. The concept of this information system design is using object-orientedapproach with UML modeling (Unified Modeling Language), and implemented withvisual basic programming languages and MySQL as database. Software developmentmethod used is Waterfall.There were some suggestions which were needed for solving those problems : 1) usingneural algorithms to make decision; 2) providing training for users of the applicationsystem; 3) developing system in the future.